Building PNM Mekar Syariah Customer Loyalty By Improving Service Quality, Trust, And Satisfaction - Putri, Thesa Irda; Sarmigi, Elex; Saleh, Muhammad Aunurrochim Mas'ad (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study aims to analyze the effect of service quality and trust on customer loyalty, with satisfaction as an intervening variable, at PT PNM Mekaar Syariah Branch in Kerinci. This research adopts a quantitative approach, utilizing a causal method, where primary data are collected through an online questionnaire using Google Forms. The population in this study consists of customers of PT PNM Mekaar Syariah, Kerinci branch, with a sample of 85 respondents selected using a convenience sampling technique. Data analysis is performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS 3.2.9. The results indicate that service quality has no significant effect on either customer loyalty or satisfaction. In contrast, trust has a positive and significant impact on both customer loyalty and satisfaction. Additionally, trust can mediate the relationship between service quality, customer satisfaction, and loyalty. However, satisfaction does not mediate the relationship between trust and service quality, nor does it mediate the relationship between service quality and customer loyalty. These findings emphasize that trust is the key factor in building customer loyalty at PT PNM Mekaar Syariah. At the same time, service quality and satisfaction have not shown a significant direct effect on loyalty.